The last time I saw her [large type] : a novel - Robards, Karen (Wheeler Publishing Large Print, A part of Gale, Cengage Learning, 2015)
"The fourth installment in the New York Times bestselling paranormal romantic thriller series featuring serial killer expert Dr. Charlotte Stone and her ghost lover, Michael Garland. While cracking the case of a cold-blooded serial killer in Las Vegas, Dr. Charlotte Stone comes close to losing the one thing she never thought she'd miss: Michael Garland, the ever-present, fatally sexy ghost who goes wherever she does. When Michael is wounded by a hostile specter, Charlie only barely saves him in time. Though she'd never admit it out loud, nearly losing Michael has made her realize just how head-over-heels in love with him she's fallen. And since Michael seems to have made a habit out of saving her life, despite the toll it's taking on his not-so-immortal soul, keeping him around means staying out of trouble. Not so easy when FBI Special Agents Tony Bartoli, Lena Kaminsky, and Buzz Crane need her help solving a particularly gruesome case - while only Tony knows about her ability to see the ghosts of the recent, violently departed, the whole team knows Charlie's the first one to call to catch a serial killer. Can Charlie track down the killer without jeopardizing her own life - or Michael's?"--